Analysis Of Discipline, Organizational Culture and Public Service Performance : Analisis Disiplin, Budaya Organisasi dan Kinerja Pelayanan Publik - Adi Sujito, Nazelia Lestari; Firdaus, Vera (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to examine the influence of the work environment, work discipline, and organizational culture on employee performance. This study uses a quantitative approach with a descriptive method. The sampling technique used was proportional stratified random sampling. The sample used in this study amounted to 236 employees. Data analysis techniques used the SPSS Statistical Package for the Social Sciences